Dopamine Receptor Pharmacology: Interactions with Serotonin Receptors and Significance for the Aetiology and Treatment of Schizophrenia - Werkman, T. R.; Glennon, J. C.; Wadman, W. J.; McCreary, A. C. (CNS & Neurological Disorders - Drug Targets, 2006)
The classification of dopamine receptors proposed more than two decades ago remains valid today. Based on biochemical and pharmaceutical properties two main classes of dopamine receptors can be distuinguished: D1-like (D1, D5) and D2-like (D2, D3, and D4) dopamine receptors. Dopamine receptors belong to the class of G protein-coupled receptors and signal to a wide range of membrane bound and intracellular effectors such as ion channels, secondary messenger systems and enzymes. Although the pharmacological properties of ligands for D1-like and D2-like dopamine receptors are quite different, the number of selective ligands for each of the five receptors subtypes is rather small. Many drugs used to treat neurological and neuropsychiatric disorders like Parkinson's disease, restless leg syndrome and schizophrenia have affinities for dopamine receptors. Such medications are not without limitations so the development of novel (selective or aselective) dopamine receptor ligands is of the utmost importance for improved therapeutic approaches for these diseases. In that respect it is also important to understand how dopamine receptor ligands affect receptor signalling processes such as desensitization, receptor heterodimerization and agonist-receptor trafficking, issues which will be discussed in the present review. Furthermore, attention is paid to interactions of dopamine receptors with serotonin receptors since many drugs used to treat above mentioned disorders of the brain also posses affinities for serotonin receptors. Because of the enormity of this area we have tried to focus more specifically on interactions within the prefrontal cortex where it appears that the serotonergic modulation of dopaminergic function might be very relevant to schizophrenia.
Keywords: dopaminergic drugs